How substantive corporate social responsibility attributions promote employee work engagement: A triple mediation model - Guo, Hao; Yan, Aimin; He, Xiaoxing (Frontiers in Environmental Science, 2022)
Increasing evidences suggest that employees exhibit positive attitudinal and behavioral responses when they attribute their company's demonstrations of corporate social responsibility as substantive. However, there has been insufficient investigation into the underlying psychological processes through which substantive corporate social responsibility attributions are associated with work engagement. Based on the model of psychological conditions for engagement, we proposed that attributions of substantive CSR are positively related to work engagement via work meaningfulness, psychological safety, and organization-based self-esteem. We collected two-wave time-lagged questionnaire data from 503 fulltime employees in mainland China. Hierarchical regression was conducted to test hypothesized model using SPSS Process macro. Results indicated that substantive corporate social responsibility attributions positively predicted work engagement; work meaningfulness, psychological safety and organization-based self-esteem parallel mediated this relationship. The findings contribute to the literature of well-being related outcomes of corporate social responsibility attributions and help a thorough understanding of antecedents of work engagement. It expands our knowledge of the new mechanisms in the relationship between corporate social responsibility attributions and work engagement. Our findings also could shed lights on the management for employees’ work engagement.